Analisa Pelatihan dan Pengembangan Sumber Daya Manusia pada PD. BPR Bank BAPAS 69 Kabupaten Magelang - Rendha Wahyu Pratiwi; Budi Hartono (CAPITAL: Jurnal Ekonomi dan Manajemen, 2021)
This study aims to explain the training analysis and development of existing PD. BPR BANK BAPAS 69 Magelang Regency. This study explains the analysis of needs, methods, types, objectives and benefits, as well as evaluating training and development. This study uses a qualitative approach, with data collection methods using observation, interviews, and documentation techniques. The results of this study indicate that the purpose of training and development is to improve the quality of human resources they have and is also useful for encouraging the progress of individuals and organizations. PD. BPR BANK BAPAS 69 uses organizational needs analysis, using two training and development methods, namely the classroom and simulation methods. The training and development carried out is formal or official because it has been planned by the organization. The evaluation is based on the value obtained from the trainer, then reviewed further and then used as material for consideration of determining career path or promotion.